HUBUNGAN ANTARA KEMANTAPAN AGREGAT DENGAN KONDUKTIFITAS HIDRAULIK JENUH TANAH PADA BERBAGAI PENGGUNAAN LAHAN DI DESA TAWANGSARI KECAMATAN PUJON, MALANG - Neni Isnawati; Endang Listyarini (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2018)
Land use system is a system that leverages the potential of a land to make ends meet. The difference in land use will have properties of both qualitative as well as quantitative different including soil quality. The organic-C of soil is one of the impacts of different land uses. The number of inputs of organic matter will affect the aggregation process on the ground. High level low level inputs of organic matter and aggregate stability will affect the value of the weight of the contents. This study was carried out at the Tawangsari village, Pujon district, Malang Â to elucidate the value of aggregate stability, soil saturated hydraulic conductivity and the nature of the relationship between them. The result value of the aggregate stability of natural forest land use had an average high of 3,79 mm, followed by land uses of forest plantation, fruit plantations and intensive farming. The result value was highest soil saturated hydraulic conductivity in protected forest, followed by the initial production, plantation forests and moorland. Agregate stability and soil saturated hydraulic conductivity had strong relation up to 40%.Â